Delft design guide : perspectives-models-approaches-methods - van Boeijen, Annemiek, ....-; Daalhuizen, Jaap, ....-; Zijlstra, Jelle, ....- (Amsterdam : BIS publishers, 2020)
Delft Design Guide provides an overview of the perspectives, models, approaches, and methods used in the bachelor's and master's curriculum of Industrial Design Engineering at Delft University of Technology (TU Delft). Some of these are unique to the university, others are well known and are used by designers worldwide. Designing products and services at this faculty is considered a systematic and structured activity, deliberately and purposefully, and with moments of increased creativity. The methods and techniques are each described in a practical one-page text, illustrated for further clarification and enriched with images that should encourage reflection and further reading. Design students can use the book as a reference guide in their design projects and in managing their personal development. Design teachers can use the book as a reference guide to assist students in learning a method. Design professionals can use the book as a reference guide to support their design processes.
Keywords: Design